Scratch Quiz Game Development using AppsGeyser - Syarifuddin; Fauzan Putraga Albahri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2022)
The aim of the research is to develop a Scratch Quiz Game using AppsGeyser. The method used in this research is Design and Creation, which is a research method that describes and creates a new product. The steps in this method are Awareness, Suggestion, Development, Evaluation and Conclusion. It is known that the research results have succeeded in designing a Scratch Quiz game using AppsGeyser. The stages carried out from the initial stages of research, development by applying the GDLC (Game Development Life Cycle) development method starting from the initiation, pre-production, production, testing, beta, and release stages until testing has been carried out. The test results show that 57% can understand the meaning of the game being tested without the need for direction by the game maker, 82% agree that the display is attractive, 64% of every game question has the correct answer, 71% of students agree that the application can replace class exams conventional, but on the question of whether students can make applications similar to AppsGeyser, they answered % stating that students still do not understand in making similar game applications.